ANTESEDEN, KARAKTERISTIK KOMUNITAS VIRTUAL DAN KONSEKUENSI BRAND COMMUNITY COMMITMENT PADA KOMUNITAS FUJIGUYS SURABAYA - Novelia Asita Mranani; Siwidyah Desi Lastianti (Media Mahardhika, 2021)
The way companies to attract customers and to strengthen relationships with customers is by using a strategy of creating a brand community within consumers. Communities are formed by various goals, views and an understanding of knowledge creates processes. The purpose of this study is to determine the effect of brand community affect, brand community trust, consumer-brand, consumer-other consumers, quality of information, quality of system, interaction and reward for activities on brand community commitment, and to determine the effect of the consequences of brand community. commitment. The sample of this research is members of the Fujiguys Surabaya community, with a total sample of 100 respondents. The analysis technique uses SEM (Structure Equation Model) with PLS (Partial Least Squares) program or software. The results showed that of the 11 hypotheses all of them had a positive and significant effect, there were only 4 hypotheses that had no positive and significant effect. Among others, brand community affect has no positive and significant effect on brand community commitment, consumer-brand has no positive and significant effect on brand community commitment, quality of information has no positive and significant effect on brand community commitment and reward for activities has no positive and significant effect on brand community commitment. brand community commitment.